Conflict Management on Employee Performance in Public Organizations - Djamil Hasim; Dahlan Dahlan; Hermanu Iriawan (Universitas Negeri Makassar, 2021)
Conflicts that occur will cause two consequences: conflicts that can be profitable and conflicts that can harm public organizations. Therefore, in the Local Government of Barru Regency, conflict management is needed to overcome everything. The purpose of the research is to determine the level of conflict management and performance of the Regional Government of Barru Regency employees, using quantitative research methods. In this study, there were 97 respondents. Data collection used include questionnaires, interviews, and documentation. The present study applied product-moment correlation analysis using SPSS software. The results of the study showed that the indicators used in each variable showed conflict management conducted in the Barru District Government obtained a result of 77.86 percent with a good category, for the performance level of employees obtained a result of 79.78 percent with a good category.